The impact of SLCO1B1 polymorphisms on homocysteine concentrations: evidence for a stronger association in men - Hu, Xinyuan; Jiang, Yanfang (Frontiers in Nephrology, 2025)
BackgroundHomocysteine (Hcy) is a risk factor for stroke. In this study, we investigated the relationship between gene polymorphisms, particularly SLCO1B1 and homocysteine (Hcy) concentrations in ischemic stroke patients, with a focus on identifying potential risk factors for elevated Hcy levels.MethodsA total of 177 ischemic stroke patients, including 99 with single nucleotide polymorphisms (SNPs), underwent pharmacogenomics (PGx) sequencing tests, from September 2022 to November 2023 at the hospital. Logistic regression analysis was used to analyze the relationship between clinical characteristics, SNPs, and Hcy concentrations. In the sub-study, 207 ischemic stroke and 244 non-stroke patients underwent SLCO1B1c.521T>C polymorphism to further demonstrate the role of SLCO1B1c.521T>C polymorphism and homocysteine.ResultsHigher Hcy concentrations were observed in men compared to women. Univariate logistic analysis identified gender, GGT concentrations, B12 concentrations, folic acid concentrations, and SLCO1B1 c.521 CC+CT polymorphism as risk factors for elevated Hcy. Multivariate logistic analysis confirmed that B12 concentrations, folic acid concentrations, and SLCO1B1 CT + CC polymorphism were significant dependent risk factors. In the sub-study, SLCO1B1 CT + CC polymorphism and the male sex were identified as risk factors for Hcy, with the effect of SLCO1B1 polymorphism being more pronounced in men.ConclusionFolic acid and vitamin B12 reduce Hcy concentrations, while the SLCO1B1 CT and CC polymorphisms are associated with higher Hcy levels. The impact of SLCO1B1 gene polymorphism on Hcy is notably stronger in the male population, suggesting that genetic factors play a significant role in determining Hcy levels.